Product Quality, Packaging, Taste, and Price as Antecedents of Consumer Satisfaction: A Case Study on Olive Fried Chicken in Yogyakarta City - Muhammad Fadli; Alfina Zsazsa Naqiya; Sukardi Sukardi (Universitas Bangka Belitung, 2024)
This study aims to analyze product quality, packaging, taste, and price on consumer satisfaction of Olive Fried Chicken consumers. The population in this study were people who had consumed Olive Fried Chicken in Yogyakarta City. The sample in the study was 150 respondents. This study used a quantitative approach. The data collection method used a questionnaire that had been tested for validity and reliability. The data analysis technique used to answer the hypothesis was multiple linear regression T-test and F-test. The results of this study indicate that product quality has a positive and significant effect on consumer satisfaction, packaging has a positive and significant effect on consumer satisfaction, taste has a positive and significant effect on consumer satisfaction, price has a positive and significant effect on consumer satisfaction and shows that product quality, packaging, taste and price have a simultaneous effect on consumer satisfaction. The R square value of 0.812 indicates that the ability of the independent variable to explain the variation of the dependent variable is 81.2% and the remaining 18.8% is explained by variables outside the research model.